2013
DOI: 10.1136/bmjqs-2013-001947
|View full text |Cite
|
Sign up to set email alerts
|

Culture and behaviour in the English National Health Service: overview of lessons from a large multimethod study

Abstract: BackgroundProblems of quality and safety persist in health systems worldwide. We conducted a large research programme to examine culture and behaviour in the English National Health Service (NHS).MethodsMixed-methods study involving collection and triangulation of data from multiple sources, including interviews, surveys, ethnographic case studies, board minutes and publicly available datasets. We narratively synthesised data across the studies to produce a holistic picture and in this paper present a high-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
404
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 350 publications
(429 citation statements)
references
References 24 publications
6
404
1
1
Order By: Relevance
“…This paper draws on a wider research programme on quality and safety in the NHS (for an overview, see Dixon-Woods et al, 2013). The study received approval from the Leicestershire, Northamptonshire and Rutland Research Ethics Committee.…”
Section: Setting and Methodsmentioning
confidence: 99%
“…This paper draws on a wider research programme on quality and safety in the NHS (for an overview, see Dixon-Woods et al, 2013). The study received approval from the Leicestershire, Northamptonshire and Rutland Research Ethics Committee.…”
Section: Setting and Methodsmentioning
confidence: 99%
“…In order to avoid negative feedback there was a demonstrated tendency to distance themselves from frontline staff, in addition concerns raised or critical comments were perceived as merely as 'whining or disruptive behaviour. ' 37 What is clear is that the 'deaf affect' to internal reporting is certainly prevalent in healthcare and as speculated by Mannion 1 are correct in their call for a strategy to deal with the resistance to bad news by those in a position of power. However, this should be considered as part of an overall strategy to improve patient safety and clinical governance and not framed as whistleblowing strategy.…”
Section: Commissions Of Inquiry Both In the United Kingdom -Public Inmentioning
confidence: 99%
“…What seems to be unknown at this time are the human factors involved in the behaviours of healthcare managers who distance themselves from staff who raise concerns about patient safety. In an examination of management and executive action in the United Kingdom's NHS, Dixon-Woods et al 37 found that while considerable time and resources had been invested into data collection and monitoring systems, the degree to which this was 'translated into actionable knowledge, and then into effective organisational responses' relied on the particular human responses of managers and or executive. DixonWoods et al 38 large mixed method research program involved 7 substudies which included data from 107 interviews with senior level stakeholders involved in quality and safety, 197 interviews with executive, board members and frontline clinicians, 715 surveys, 2 focus groups, and 10 interviews with patients and the public, patient and staff satisfaction survey data from 2005-2011 and 621 clinical teams assessed using Aston Team Performance Inventory.…”
Section: Commissions Of Inquiry Both In the United Kingdom -Public Inmentioning
confidence: 99%
“…Although the nature of a REA means that it is unlikely to include all the relevant literature related to the search question and some papers may not have been identified, [28] the material retrieved and considered in the review suggests that a reasonable balance between comprehensiveness and timeliness has been achieved. [25] The papers included report empirical data, in the main, and provide some useful insights on the issues involved in supporting staff in caring roles which is an important international issue because a number of countries including England, New Zealand, the USA and the Netherlands have experienced organisational crises in healthcare resulting in failures in care [90] which arise, in part from lack of staff support. For example, Martin and Dixon-Woods [91] argue that if the lessons from a major hospital failure in England are to be learned then the seemingly straightforward solutions that characterise the problem as arising from poor performance in one hospital, or from "bad apple" staff need to be rejected, along with analyses that regard such occurrences as inevitable.…”
Section: Discussionmentioning
confidence: 99%